Pengembangan Media LKPD Sejarah untuk Meningkatkan Hasil Belajar Siswa Kelas XI MAN 2 Lubuklinggau - Weni Weni; Andriana Sofiarini; Agus Susilo (CV. Alim's Publishing, 2026)
This study aimed to develop a History LKPD on the topic of the Proclamation of Indonesia Independence that met the criteria of validty, practicality and effectiveness for grade XI students at MAN 2 Lubuk linggau. This research employed the Research and Development (R&d) method using the ADDIE development model, Which consists of five stages: Analysis, Design, Development, Implementation, and evaluation. Data were collected throught observations. Interviews, questionnaires, and test. The data were analyzed using Aikens’V indeks to measure validity, percentage analysis to determine practicality, and the N-gain test to measure the effectiveness of the developed prodect. The results showed that the developed History LKPD obtained Aiken;s V scores of 84 from the material expert (highly valid), 0,73 from the media expert (valid), and 0,83 from the language expert (highly valid). The practicality test showed teacher and student response percentages of 96%, indicating that the LKPD was highly pratical. Furthermore, the effectivenees test resulted in an N-Gain score of 0.71, which was categorized as high, indicating that the developed LKPD effectively improved student’ learning outcomes. Based on these findings, it can be concluded that the developed History LKPD fulfilled the criteria of validity, practicality, and effectiveness and is therefore suitable for use as instructional material to support History learning for grade XI students at MAN 2 lubuk linggau.